If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -4x + 5y = 0 Solving 5 + -4x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -4x + -5 + 5y = 0 + -5 Reorder the terms: 5 + -5 + -4x + 5y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x + 5y = 0 + -5 -4x + 5y = 0 + -5 Combine like terms: 0 + -5 = -5 -4x + 5y = -5 Add '-5y' to each side of the equation. -4x + 5y + -5y = -5 + -5y Combine like terms: 5y + -5y = 0 -4x + 0 = -5 + -5y -4x = -5 + -5y Divide each side by '-4'. x = 1.25 + 1.25y Simplifying x = 1.25 + 1.25y
| -4=-7z | | 3(x-1)+7=1(x+5) | | 250x=1085+120x | | .5(x-6.5)=3.16 | | 2lnx/x | | 5x-2/3=20 | | 2*x-3*y= | | 2lnx/x=0 | | 2*x-3*y=4 | | 8/s=0.2 | | (6x-11)=(25-4x) | | 3x+4x+50=2x+100 | | 3(x-8)5x+6= | | -0.75(x+3.5)=6 | | ([9x-3]/6)-([17-x]/19=([x/15]-16) | | 2y^2-y-5=0 | | -6+8x=66 | | (3x+3)(5x-2)=12 | | -8t+2=-14 | | .75(x+3.5)=6 | | -7x+5(-3+6y)-6y+3= | | -1(4(d+3)-5(3d-2(2d+7))-8)=-10d-6 | | 16z^2-20z=0 | | z^2-12z=-27 | | e^5-4x=890 | | 15x^5y^2/20x^10y^-7 | | .25x+.5y=29 | | 3*x-4=20 | | x=1.2+-1.6y | | 2*x+5=19 | | f(x)=-2x-2+1 | | 3(3x+12)=x+4 |